Chronic impedance spectroscopy of an endovascular stent-electrode array. (5th July 2016) - Opie, Nicholas L; John, Sam E; Rind, Gil S; Ronayne, Stephen M; Grayden, David B; Burkitt, Anthony N; May, Clive N; O'Brien, Terence J; Oxley, Thomas J
Abstract: Objective. Recently, we reported a minimally invasive stent-electrode array capable of recording neural signals from within a blood vessel. We now investigate the use of electrochemical impedance spectroscopy (EIS) measurements to infer changes occurring to the electrode–tissue interface from devices implanted in a cohort of sheep for up to 190 days. Approach. In a cohort of 15 sheep, endovascular stent-electrode arrays were implanted in the superior sagittal sinus overlying the motor cortex for up to 190 days. EIS was performed routinely to quantify viable electrodes for up to 91 days. An equivalent circuit model (ECM) was developed from the in vivo measurements to characterize the electrode–tissue interface changes occurring to the electrodes chronically implanted within a blood vessel. Post-mortem histological assessment of stent and electrode incorporation into the wall of the cortical vessels was compared to the electrical impedance measurements. Main results. EIS could be used to infer electrode viability and was consistent with x-ray analysis performed in vivo, and post-mortem evaluation. Viable electrodes exhibited consistent 1 kHz impedances across the 91 day measurement period, with the peak resistance frequency for the acquired data also stable over time. There was a significant change in 100 Hz phase angles, increasing from −67.8° ± 8.8° at day 0 to −43.8° ± 0.8° at day 91, which was observed to stabilize after eight days. ECM's modeled to the data suggested this change was due to an increase in the capacitance of the electrode–tissue interface. This was supported by histological assessment with >85% of the implanted stent struts covered with neointima and incorporated into the blood vessel within two weeks. Conclusion. This work demonstrated that EIS could be used to determine the viability of electrode implanted chronically within a blood vessel. Impedance measurements alone were not observed to be a useful predictor of alterations occurring at the electrode tissue interface. However, measurement of 100 Hz phase angles was in good agreement with the capacitive changes predicted by the ECM and consistent with suggestions that this represents protein absorption on the electrode surface. 100 Hz phase angles stabilized after 8 days, consistent with histologically assessed samples. Significance. These findings demonstrate the potential application of this technology for use as a chronic neural recording system and indicate the importance of conducting EIS as a measure to identify viable electrodes and changes occurring at the electrode–tissue interface.